Gully erosion assessment and growth prediction on military training lands - Corkins, Chelsea Rose (Kansas State University, 2013)
Military maneuvers result in significant physical and environmental impacts to the landscape. These impacts generally result in a loss of vegetative cover and increased watershed runoff and rate depending on vehicle speed, turning radius, and soil moisture content. Unless adequately monitored or mitigated, this increased runoff can lead to excessive soil erosion and gully formation. Past studies have revealed that these gullies can impact water quality from excessive erosion and create concerns regarding soldier safety. In order to better understand how gullies form and evolve overtime on military installations, a study is being conducted at Fort Riley, KS. In 2010, approximately forty gullies were identified, assessed, and measured using common erosion monitoring and surveying techniques. These gully locations, and any newly formed gullies, were remeasured using these same methods in 2012 to determine the rate of growth for each site with respect to width, depth, and headcut. Of fifty-nine gullies total, twenty one were initially included in this study. Upon further analysis including the utilization of watershed characteristics and land management techniques, eleven of the 21 utilized gullies were deemed appropriate to include in predictive assessment, as these eleven systems exhibited singular headcut migration. Multiple Regression Analysis was utilized to produce predictive equations for Headcut Growth. This equation [Headcut Growth = 0.666 + 0.137(Watershed Slope) – 0.478(Training Intensity) + 0.757(log[Watershed Area]) – 0.278(Drainage Density) – 0.0138(Above Ground Biomass Change) + 0.187(Burning Frequency] resulted in a model relationship of approximately 90%, with Watershed Slope being the most significant variable when an output Headcut Growth was reached.
Keywords: Gully erosion; Military; Erosion prediction; Environmental Engineering (0775)